KNOWLEDGE, ATTITUDE AND PERCEPTION OF HIV, ART AND PMTCT AMONG HIV INFECTED PREGNANT WOMEN IN NAROK SUB-COUNTY HOSPITALS - Gakii, Jackline; Maoga, PhD., Dr. Winfreda Nyamota; Menza, PhD., Dr. Nelson (Global Journal of Health Sciences, 2019)
Purpose: The purpose of the study was to determine knowledge, attitude and perception of HIV, ART and PMTCT among hiv infected pregnant women in Narok Sub-County Hospitals Methods: The study was a cross-sectional study using simple random sampling method to sample the required sample size for the study of 117 HIV infected pregnant women. The study was conducted in all Narok sub-county hospitals. Semi-structured questionnaire was used to collect quantitative data. Focused group discussions and key informant interviews were used to collect qualitative data. Data entry and coding was done in SPSS v21. Descriptive statistics was used to compute proportions, mean and standard deviation. Qualitative data was categorized into themes based on the study objectives. To test the association between dependent and independent variables logistic regression analysis was used to generate odds ratios of association. Results: Knowledge of HIV, ART and PMTCT and good attitude and perception towards HIV, ART and PMTCT services among HIV+ pregnant women are predictors of retention in care among HIV positive women. Unique Contribution to Theory, Practice and Policy: The study recommeded that the Ministry of Health and other stakeholders should hold community awareness and sensitization programmes on benefits of PMTCT services to pave way for acceptance and hence use and prevent vertical and horizontal transmission of HIV.